Kewajiban Menuntut Ilmu dan Hakikat Pendidikan Perspektif Hadis - Harmansyah Ramadhan; Salsabila Matondang; Riska Khadijah (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2023)
This research is motivated by various conceptions about education in Islam. Islamic education turns out to have a unique meaning contained in the Hadith because it shows the richness of the meaning of words in every sentence. The purpose of this study is to find out how the obligation to study and the nature of education from the perspective of hadith. The research method used is library research and is qualitative descriptive analysis with a philosophical approach. The data analysis used is the Miles and Huberman analysis model, namely collecting data, reducing data, presenting data, and drawing conclusions. The results of this research are from the results of deliberations at the first world Islamic education international conference held by King Abdul Aziz University in Jeddah, it was agreed that there are three terms of education in Islam, namely at-Ta-lim, at-Tarbiyah, and at- Ta'dib. Ta'lim from the perspective of hadith explains the obligation to study, the virtues of knowledgeable people, and the benefits of knowledge for the owner. Furthermore, tarbiyah from the perspective of hadith, explains that tarbiyah is a process of educating, fostering, and maintaining. While ta'dib is an attempt to train and get used to good behavior. The terms ta'lim, tarbiyah, and ta'dib have several meanings, but all three are implicitly related to one another.